Role model nursing instructors and facilitation of students' professional growth process: Directed content analysis - Marzieh Azadian; Tahereh Nasrabadi; Abbas Ebadi; Jamileh Mokhtari Nouri (Wolters Kluwer Medknow Publications, 2024)
Background: The professionalization of nursing is one of the goals of academic education, which needs to be nurtured during education, so this research was conducted to study the views and experiences of nursing students and instructors regarding professional growth through role mode nursing instructors. Materials and Methods: This was a qualitative study with directed content analysis based on the growing up and role modeling theory in nursing students' education, which was conducted at two universities in Iran from April to September 2021. The participants included 16 undergraduate, master's, and PhD students, and nursing instructors selected using purposeful sampling with maximum diversity. The data were collected through in-depth interviews. Results: From the data analysis, 689 unrefined primary codes and 76 integrated codes were extracted. The three subcategories of the previous study included "effort to improve educational quality," "clinical effectiveness," and "promotion of professional status." Generic categories were formed based on the grouping of codes. "Effort to improve educational quality" included the six generic categories of educational effectiveness, effective classroom management, comprehensive evaluation, adherence to educational rules, application of knowledge, and efforts to promote research. "Clinical effectiveness" included the generic category of effective clinical training. "Promotion of professional status" included the two generic categories of effective professional interactions and striving for professional independence. Conclusions: It can be concluded that role model nursing instructors can increase the students' abilities, and thus, facilitate their professional growth through a combination of strategies based on the generic categories mentioned.